Optimasi Proses Pembuatan Tepung Asap - Purnama Darmadji (agriTECH, 2002)
Experiments were performed to optimize the process of smoke powder production using liquid smoke of coconut shell as raw material and rice powder as a model system for filler of smoke posder. The liquid smoke was produced by pyrolization method and the purification of the liquid smoke was done by redistillation method. The redistilled liquid smoke was diluted with varied water and mixed with some ratio of rice powder. The sensories of smoke powder was evaluated for ador, taste and overall, and data were optimized using Response Surface Methodology.The result of optimization process on the production of smoke powder indicated that the optimum temperature for redistillation process were 160ºC, the ratio of redistilled liquid smoke and rice powser was 2.5 ml/ 50 gram, and the concentration of the liquid smoke was 15.1%. The confirmation of the optimization value indicated that smoke powder was acceptable for consumer.